Oceanography and Marine Biology An Annual Review, Volume 58 - Hawkins, S. J.; Allcock, A. L.; Bates, A. E.; Evans, A.J; Firth, L. B.; McQuaid, C. D.; Russell, B. D.; Smith, I. P.; Swearer, S. E.; Todd, P. A. (Taylor & Francis, 2020)
Oceanography and Marine Biology: An Annual Review remains one of the most cited sources in marine science and oceanography. The ever-increasing interest in work in oceanography and marine biology and its relevance to global environmental issues, especially global climate change and its impacts, creates a demand for authoritative refereed reviews summarizing and synthesizing the results of recent research. For more than 50 years, OMBAR has been an essential reference for research workers and students in all fields of marine science. This volume considers such diverse topics as optimal design for ecosystem-level ocean observatories, the oceanography and ecology of Ningaloo, human pressures and the emergence of novel marine ecosystems and priority species to support the functional integrity of coral reefs. Six of the nine peer-reviewed contributions in Volume 58 are available to read Open Access via the links on the Routledge.com webpage. An international Editorial Board ensures global relevance and expert peer review, with editors from Australia, Canada, Hong Kong, Ireland, Singapore, South Africa and the United Kingdom. The series volumes find a place in the libraries of not only marine laboratories and oceanographic institutes, but also universities worldwide.